Spain : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that the Spanish economy accumulated large imbalances during the long boom that ended with the global financial crisis. Unemployment soared, the fiscal position deteriorated sharply, and funding conditions tightened for both the public and private sectors. Key imbalances are correcting rapidly. Growth has been negative in the last seven quarters, unemployment has reached high levels, and financing conditions remain tight for small firms. The reform process has accelerated and deepened. Decisive reforms in the labor, financial, and fiscal sectors, in line with past IMF staff recommendations, is helping stabilize the economy.